Differential Pursuit-Evasion Game Strategy Design for Spacecrafts Under Electromagnetic Interference Attack: Theory and Semiphysical Experiment - Yuan, Huanhuan; Yuan, Yuan; Xia, Yuanqing (IEEE/ASME transactions on mechatronics, 2025)
This article investigates the orbit pursuit-evasion game issue with three spacecrafts including one communication spacecraft pair and one jamming spacecraft. The jamming spacecraft maneuvers autonomously to pursue the communication spacecraft pair and meanwhile launches electromagnetic interference to destroy the quality of transmitted signal between two spacecrafts. The communication spacecrafts maneuver autonomously to evade the destruction from the jamming spacecraft. That is, the jamming spacecraft aims to minimize the capability of communication spacecrafts with jointly minimum maneuver and interference power consumption. While, the communication spacecraft pair targets at maximizing the communication capability with as little maneuver power consumption as possible. The cyber-physical coupled pursuit-evasion relationship between jamming and communication spacecrafts is constructed as a zero-sum dynamic differential game. The existence of Nash equilibrium solution is verified and the solution of zero-sum game is found by leveraging the Pontryagins minimum principle. Finally, both numerical simulation and semiphysical experiment are presented to evaluate the effectiveness of the game and NE solution.